Factor structure of the Indonesian version of the Parent as Social Context Questionnaire - Fitri Ariyanti Abidin; Rismijati E Koesma; Poeti Joefiani; Juke Roosjati Siregar (Universitas Ahmad Dahlan, 2019)
The use of a dimensional approach in assessment tools of parenting style in Indonesia is still very limited. Parent as Social Context Questionnaire (PSCQ)-Adolescent Report is widely known as a dimensional-parenting style assessment tool. This study examined the factor structure and reliability of the Indonesian version of the PSCQ-Adolescent Report. This 24-item questionnaire measures six parenting dimensions: warmth, structure, autonomy support, rejection, chaos, and coercion, with four items in each dimension. Participants were 1476 Junior High School Students aged 11-16 years old (48% male, 52% female), recruited from six main islands in Indonesia. Our findings confirmed the original six unipolar factor structures of the Indonesian PSCQ. Of the six factors, five factors with the exception of coercion had acceptable to good reliability. The finding that coercion had no negative correlation with the positive dimensions such as warmth and autonomy support differs from findings in the West, indicating that coercion is considered negative in Western culture but is not the case in Indonesia. This study concluded that PSCQ-Adolescent Report can be used as a valid and reliable measure of the parenting style of Indonesian adolescents.